Experimental Study of Action Different Kinetic Energy on the Colon - Kvasnevskyi, Yevhen; Kashtalian, Michailo; Gerasimenko, Oleh; Kvasnevskyi, Oleksandr (Lietuvos chirurgija, 2022)
The purpose of the study. To increase the effectiveness of surgical care for the wounded with combat trauma of the colon by studying of ballistic, morphological and functional features of the gunshot wounds. Patients and methods. A study of surgical treatment of 83 wounded with combat injuries of the colon, received in the area of anti-terrorist operation in the period from 2014–2018. For comparative analysis of treatment results, two clinical groups were formed: comparison and main. The comparison group included 42 wounded who were treated from April 2014 to February 2015 (the first and second periods of ATO), who used traditional surgical tactics. The main group included 41 wounded who were treated from March 2015 to 2018. Results. Analysis of the distribution of wounded with combat trauma by type of wound / injury revealed that the vast majority of them in both groups had shrapnel wounds – 49 (59.1%). There were 30 (36.1%) victims with bullet wounds, and 4 (4.8%) with closed injuries. The wounded patients with the battle trauma of the thick bowel by type of injury had missile wounds as a rule – 49 (59.1%). There were 30 (36.1%) patients with bullet wounds, and 4 (4.8%) with closed injuries. Most of the injuries were combined – 58 (69.9%), and with only abdominal injuries – 25 (30.1%), mostly multiple – 21 (25.3%). The great majority of the thick bowel injuries belonged to sigmoid – 32 (38.6%) and transverse colon – 21 (25.3%), which is explained by relatively large size of these parts of the intestine. Conclusions. The choice of surgical tactics and scope of surgical interventions on damaged organs and structures took into account the results of experimental study of mechanogenesis and pathomorphology of gunshot wounds of the colon, obtained in bench studies by modeling gunshot wounds on “thoracoabdominal ballistic material”.